Formation age and geological environment of monzonitic granite from Qingshanpu pluton on the eastern margin of Longshou, Gansu. Issue 2 (July 2021) - Zhu, Quanlong; Guo, Zhifeng; Wang, Shengyun; Chen, Jinyong; Qiu, Ruizhao; Zhou, Su
Abstract: Zircon U–Pb dating, geochemistry, and Sr–Nd–Hf isotope data are reported for monzonite from the Qingshanpu pluton on the eastern margin of Longshoushan. The zircon LA-ICP-MS U–Pb age data showed that the emplacement age of the monzonite is 442.6 ± 4.8 Ma. The rocks are characterized by high SiO2 contents (73.15%–73.85%), high K2 O contents (3.67%–3.99%), and low P2 O5 contents (0.042%–0.049%). The aluminum saturation index was 1.03–1.05, and the molecular number of standard corundum was 0.58%–0.77%. Rocks are enriched in Rb, Sr, U, K, and Pb and depleted in Nb, Ti, Zr, P, and Eu, thereby indicating that they are weakly peraluminous I-type granites. The monzonite in the Qingshanpu pluton had lower ISr values, which ranged from 0.70850 to 0.70904, and the εNd(t) values ranged from -8.54 to -6.49. The εHf(t) values ranged from -9.75 to 0.42, and the two-stage model age T C DM ranged from 1406 to 2043 Ma. This study concluded that the North Qilian subducted beneath the Alxa Plate at the end of the Early Paleozoic, causing elastic collision and eventually leading to closure. During elastic collision, several parts of the orogenic belt collapsed and were dismantled. The remelted ancient crust mixed with a small amount of mantle material during its ascent and finally formed the Qingshanbao pluton.